EARLY PLEISTOCENE FAUNAS OF SMALL MAMMALS IN EASTERN EUROPE - Markova A.K. (My University, 1999)
Materials from many lower Pleistocene localities of small mammal remains elucidate principal stages of the fauna evolution in eastern Europe and enable the biostratigraphic subdivision of host deposits on the basis of evolutionary changes in small mammal communities and their coordination with geological and geochronological data. Several assemblages and evolutionary phases of early Pleistocene mammals are distinguished. The first occurrence levels of new taxa (mostly of genera and species of Arvicolidae) are used to detect boundaries between assemblages. The established geochronological subdivisions of the Pleistocene are coordinated with those of West European scales. The initial period of the early Pleistocene and an early phase of the Odessa fauna of small mammals correspond to the first occurrence level of arhizodont vole Allophaiomys deucalion. Later faunas of the Odessa assemblage are characterized by the appearance of arhizodont vole genera Prolagurus (P. ternopolitanus) and Lagurodon (L. arankae), who had teeth lacking cementum. These taxa coexisted with Allophaiomys deucalion. The more progressive Nogaisk faunas of small mammals (Topachevskii, 1965) included the evolved species Allophaiomys pliocaenicus, which coexisted with Prolagurus ternopolitanus and Lagurodon arankae. The next stage of evolution was marked by origin of first small lemmings Prolagurus pannonicus. The term Kairy faunas is suggested to be appropriate for assemblages of this stratigraphic level (derived from the Zapadnye Kairy stratotype locality in the Dnieper River lower courses). The Kairy faunas also include voles Allophaiomys pliocaenicus, Mimomys savini, and Mimomys pusillus. These faunas are correlative in age with the paleomagnetic Jaramillo Subchron. More progressive assemblages with first Microtus (Terricola) and Microtus (Stenocranius ?) hintoni have been already described as the Morozovka faunas (Aleksandrova, 1976). Advanced Mimomys forms, Allophaiomys pliocaenicus nutiensis, and Prolagurus pannonicus are characteristic of this stratigraphic level. Successive Petropavlovka faunas of small mammals correspond in time to the end of the early Pleistocene and to the Matuyama Chron. Their index forms are first voles Microtus ex gr. oeconomus. The advanced Mimomys species (M. savini, M. pusillus) of the Petropavlovka faunas coexisted with dominant Prolagurus pannonicus, Eolagurus argyropuloi, and Microtus (Stenocranius) hintoni. The early Tiraspol faunas correlative with the uppermost level of the Matuyama Chronozone are distinct because of newcomers Microtus arvalinus and Prolagurus posterius.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен